The 2nd International Laayoune Forum on Biosaline Agriculture - Hirich, Abdelaziz; Choukr-Allah, Redouane (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book showcases the advanced and emergent research in the field of biosaline agriculture from salinity mapping and plant breeding for a salinity-resistance purpose to the value-chain development of salt-tolerant crops.